Living in the shadows of schizophrenia: a qualitative inquiry into caregivers' psychosocial burden - Uslu, Omer; Durmus, Mustafa; Salik, Hava; Sahin, Merve (Routledge Journals, Taylor & Francis Ltd, 2025)
This study aimed to qualitatively examine the psychosocial burden experienced by caregivers of schizophrenic patients.This study used an interpretative phenomenological analytical design. The sample comprised 15 individuals responsible for the care of patients with schizophrenia in T & uuml;rkiye. A homogeneous sampling method, a form of purposeful sampling, was used to select the participants. Data were collected through face-to-face, semi-structured interviews, and the analysis was performed using MAXQDA 22 software.The data obtained from the interviews were analyzed under four themes: 'Challenges in the Caregiving Experience ', 'Healing Process in Cultural Context' and ' Coping Experiences'.This study elucidated the complex challenges encountered by caregivers of patients with schizophrenia. Consistent with these findings, it is imperative to implement comprehensive policies that incorporate cultural sensitivity and gender equality to mitigate the difficulties experienced by caregivers of schizophrenic patients.
Keywords: Caregivers; Qualitative Research; Psychosocial Burden; Schizophrenia